Fears of Visually Impaired Pre-School Children and Their Parents - Gudonis, Vytautas; Kaffemanienė, Irena; Radzevičienė, Liuda; Elijošius, Egidijus; Klopota, Yevhenii (Pedagogika, 2017)
The article analyses the fears of preschool age children, with visual impairment, and the fears of their parents. It was aimed to define whether the fears of preschool age children, with vision problems, differ from the fears of the same age children, with no vision problems. The hypothesis was formed that the parental childhood fears can be transmitted to their mature age, and present fears can be transmitted to their children. The results of the research revealed such tendencies as follows: the participating in the research preschool age children, with vision problems, do not have any exceptional fears, comparing to the children of the same age but with no vision problems; the larger number of fears reflected in those children, whose parents have a high educational level, comparing to the parents, with a lower educational level; children from incomplete families have more fears; mothers used to have less fears in childhood than they have now; the fears, children and some parents have, might have been transmitted from parents to children.